الآليات القانونية للحد من مخاطر الاعتماد المستندي - بالعروسي, خولة (University of Eloued جامعة الوادي, 2015)
المعرفة انه ليس هناك اعتماد خال كليا من المخاطر بالنسبة للمصرف مهما قدم العميل من ضمانات، وحتى ولو حرص المصرف الدقة في جميع قواعد منح الائتمان فقد يستجد من الظروف ما هو خارج عن إرادة كل من المصرف والعميل ويؤدي إلى خلق المخاطر . - إن المصارف التي تحصر اعتماداتها في فرع معين من فروع النشاط الاقتصادي أو في منطقة جغرافية واحدة تتعرض إلى مخاطر تفوق تلك التي تتعرض لها غيرها . - بالرغم من إن تقنية الاعتماد المستندي تتميز بالثقة والأمان في التعامل على أنها تتضمن عدة مخاطر كسرقة وتعرض البضاعة للتلف ومشاكل أخرى بسبب النقل مما يستوجب الحرص واتخاذ الاحتياطات اللازمةKnowing that there is no completely risk-free credit for the bank, no matter how old the customer is of guarantees, and even if the bank was keen to be accurate in all the rules for granting credit, it may come up with new guarantees Circumstances are beyond the control of both the bank and the customer and lead to the creation of risks. - The banks that limit their credits to a specific branch of economic activity or in One geographic area is exposed to more risks than others. - Although the documentary credit technology is characterized by confidence and safety in dealing as it includes Several risks, such as theft, damage to the goods, and other problems due to transportation, which necessitates Take care and take the necessary precautions
Keywords: الآليات القانونية -مخاطر- الاعتماد المستندي